Development of Self-Confidence Assessment Instruments for 7th State Junior High School Students in Banjarmasin (JED (Jurnal Etika Demokrasi), 2022)
So far, most teachers only focus on the aspect of knowledge, while the assessment of the attitude aspect is only done through the teacher's subjective observations. This study aims to develop an instrument in the form of a valid and reliable student self-assessment to measure attitudes on indicators of self-confidence.The method used is Research and Development (R&D) from Borg and Gall. This research was conducted at State Junior High School 7 Banjarmasin, with 200 students as the sample. Data collection techniques used in the form of a questionnaire. The data were analyzed descriptively quantitatively with the help of SPSS version 25 program. Of the 35 instruments that were tested on a small scale, there were 28 valid instruments and 7 invalid items because they had an rcount of 0.349 at a significance level of 5%. Of the 28 valid instruments, a large-scale trial was carried out with a sample of 200 students. The results of the analysis of 28 items using the product moment test, the results obtained that all instruments were declared valid because all of them had rcount values > 0.138. From the 28 instrument items, it was followed by a reliability test using Cronbach's alpha formula and obtained a value of 0.898 (high criteria). It can be concluded that the 28 instruments are suitable to be used to assess the self-confidence of the students of SMP Negeri 7 Banjarmasin.